Analisis Silabus Kurikulum 2013 Mata Pelajaran Fikih MTs Kelas VII - Wahyudin, Afif; Yahya, Moh. (JOIES (Journal of Islamic Education Studies), 2017)
This study uses a qualitative research approach with document analysis methods. In the process, the authors sort and group data into themes. The results of the grouping are then interpreted and evaluated. The object of the author's study is the syllabus of Fiqh for Class VII of MTs. Curriculum 2013 revised edition 2016. Aspects targeted by the author include the structure, KD pairs, number of hours, learning activities, and assessment strategies. The results of the analysis provide conclusions; (1) There is an unsynchronization between syllabus, teacher's book and student's book. (2) There is an important component that is not in the syllabus, namely the learning objectives. (2) The distribution of time allocation is still uniform in one column even though the level of concept and practice in each material weighs differently, one material weighs heavier concept while other material has heavier practice weight, and d). The main material in the syllabus is incomplete, still too global so it is difficult to translate.